Resveratrol Adding Life to Years, Not Adding Years to Life - Badria, Farid A. (IntechOpen, 2019)
This book intends to strike a balance between developments in research and the fact that researchers must absorb and link to scientific advances with clinical practice so that the management of diseases can be based on sound physiological concepts. This book addresses several controversial issues regarding a natural molecule with fascinating pharmacological and therapeutic effects. The book contains three sections: Section 1: Pharmacology and Therapeutic Applications of Resveratrol; Section 2: Bioavailability, Metabolism, and Mode of Action of Resveratrol; Section 3: Resveratrol and Its Role in Chronic and Degenerative Diseases. Does it Add Life to Years or Years to Life? It is our hope that this book will motivate readers to approach the evidence on the use resveratrol and thereby spark an interest in making further contributions to the current scientific debate and treatment development efforts.